Assessment of the Quality and Authenticity of Pesto Sauces Available on the Polish Market - Śmiechowska, Maria; Sanocka, Magdalena (Ocena jakości i autentyczności sosów pesto dostępnych na polskim rynku, 2024)
Aim: The aim of this study was to assess the quality of pesto sauces available in Poland on the Tri-City market (Gdańsk, Gdynia and Sopot). Three pesto sauces were tested: Grand’Italia pesto alla genovese (GI), SACLA Italia pesto alla genovese (SI), Baresa Pesto alla Genovese (BP). Methodology: The correctness of labelling of selected sauces was assessed in accordance with the requirements of the Regulation of the European Parliament and of the Council (EU) of 25 October 2011. The acidity of the sauces was tested using the acid-base titration method with NaOH solution against phenolphthalein. The content of NaCl salt in pesto sauces was determined using the Mohr method. The colour of pesto sauces was determined using the CIELab method using the Konica-Minolta CR 400 colourimeter. The fat content in the tested sauces was determined using the Gerber method. Results: The tested sauces contained all the information that should appear on the packaging, including the name of the product, the name and address of the manufacturer, the composition and nutritional value, the production batch number and the expiry date. The acidity of the tested pesto sauces was in the range of 2.4-3.6% in terms of acetic acid. The salt content was in the range of 2.3-2.9%, and the fat content was in the range of 38.0-42.5%. The value of the L* parameter in the analysed pesto sauces remained in a narrow range of 41.91-42.72. The value of the a* parameter was in the range of –1.83 to –2.37, the value of which depends on the degree of decomposition of chlorophyll contained in basil, which is the main component of pesto sauce. In turn, the value of the b* parameter was in the range of 22.45-26.78. The results of the study showed that the quality of the analyzed pesto sauces differed from the literature data on the production of pesto alla genovese sauces. The presence of ingredients such as simple saccharides and glucose-fructose syrup, the presence of thickening agents and the low content of Pecorino Romano or Grana Padano cheese raise concerns. Implications and recommendations: Further research on pesto sauces is necessary to ensure their quality and authenticity due to the growing interest of consumers in Italian food products. Originality/value: The conducted research is one of the few in Poland and is a contribution to the assessment of quality and ensuring the authenticity of selected pesto sauces available on the Polish market.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 62-71